MEASUREMENT INSTRUMENTS REGARDING KNOWLEDGE, ADHERENCE, ATTITUDE AND SELF-EFFICACY IN SICKLE CELL DISEASE: AN INTEGRATIVE REVIEW - Sumaya Giarola Cecilio; Valquíria dos Santos Pinto; Sônia Aparecida dos Santos Pereira; Aline de Abreu Silvestre Sales; Clarissa Fernandes Goulart; Lilian Kelen de Aguiar (Universidade Federal do Paraná, 2019)
Objective: To identify in Brazilian and international literature existing measurement instruments to measure the domains of knowledge, self-efficacy, attitude and treatment adherence in the context of sickle cell disease. Method: This was an integrative review conducted by searching articles in journals indexed in the CINAHL, LILACS, PubMed and WoS databases, according to the following inclusion criteria: original articles that used instruments to measure at least one of the studied domains (knowledge or treatment adherence or self-efficacy or attitudes of people with sickle cell disease, regardless of age of population), in the last 15 years (2003 to 2018). Results: Of the 379 articles found, 11 were included, and among these, five instruments were identified. Conclusion: The instruments identified in the literature review can provide indicators relative to the psychosocial and behavioral domains of sickle cell disease.